Breeding black sigatoka resistant plantains with a wild banana. - Swennen, R.; Vuylsteke, D. (1993)
Plantain (Musa spp., AAB group), an important staple food crop in the lowland humid tropics of Africa, Latin America, and the Caribbean, is threatened by a fungal leaf spot disease called black Sigatoka. Two African plantain cultivars of the medium French category were crossed with ‘Calcutta 4’ (Musa acuminate ssp. burmannicoides), a wild diploid banana highly resistant to black Sigatoka. Four tetraploid hybrids, selected from the progenies of the crosses, showed high levels of resistance to black Sigatoka and produced bunches up to 125% heavier than their fungicide-treated plaintain parents. The inferior fruit size of the wild banana was not reflected in these hybrids. The wild diploid ‘Calcutta 4’ can thus be in a plantain breeding programme.